Being well-in with the Joneses? A lab-in-the-field experiment on conspicuous consumption among rural communities - Lena Kuhn; Ihtiyor Bobojonov; Laura Moritz (The Journal of Development Studies, 2024)
Conspicuous consumption, specialised consumption of high visibility but without apparent economic benefit, is reducing investment in productive assets and thus hindering economic development in low-income countries. In previous research, the phenomenon was commonly explained by status-seeking and herding behaviour. Our study follows a novel angle in testing the role of risk sharing, assuming that investment into social status is perceived to increase access to informal credits in times of crises. We conduct a random-effects hurdle model along a lab-in-the-field experiment along a sample of 197 wheat farmers in Uzbekistan, a country characterised by high levels of risk and uncertainty. Within our experimental setup, both risk attitude and real-life risk management decision are found to be significant determinants of conspicuous consumption. Our findings support the notion of a complex decision-making process with risk sharing as one important motivator. Providing first empirical evidence on the topic, our findings have implications beyond our narrowly defined study case: We argue that strengthening options of formal risk-sharing tools might remove one of the motivators for conspicuous consumption; thus, it could improve the economic welfare of low-income households worldwide by allowing for more productive investment of scarce financial resources.
Keywords: D12; D14; I32; 330; conspicuous consumption; peacock effect; behavioural experiment; risk management policy; resilience; climate change mitigation